Biogeochemical properties of seawater measured from the icebreaker Shirase during the 57th Japanese Antarctic Research Expedition in the austral summer, 2015–2016 - TAKAMURA, Tomomi R.; TAKAHASHI, Kunio T.; MAKABE, Ryusuke; ODATE, Tsuneo (国立極地研究所, 2016)
Fig. 1 | http://polaris.nipr.ac.jp/~parc/pub/v025/nipr_parc_183_0001_2016.doc Fig. 2 | http://polaris.nipr.ac.jp/~parc/pub/v025/nipr_parc_183_0002_2016.doc Table 1 | http://polaris.nipr.ac.jp/~parc/pub/v025/nipr_parc_183_0003_2016.doc Table 2 | http://polaris.nipr.ac.jp/~parc/pub/v025/nipr_parc_183_0004_2016.doc Table 3 | http://polaris.nipr.ac.jp/~parc/pub/v025/nipr_parc_183_0005_2016.doc departmental bulletin paper